2013
DOI: 10.2196/jmir.2317
|View full text |Cite
|
Sign up to set email alerts
|

A Text Messaging Intervention to Improve Heart Failure Self-Management After Hospital Discharge in a Largely African-American Population: Before-After Study

Abstract: BackgroundThere is increasing interest in finding novel approaches to reduce health disparities in readmissions for acute decompensated heart failure (ADHF). Text messaging is a promising platform for improving chronic disease self-management in low-income populations, yet is largely unexplored in ADHF.ObjectiveThe purpose of this pre-post study was to assess the feasibility and acceptability of a text message–based (SMS: short message service) intervention in a largely African American population with ADHF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 19 publications
4
153
0
2
Order By: Relevance
“…To our knowledge, the literature related specifically to technology use for self-management in Blacks with heart failure is limited to four studies: one that investigates the use of an e-Health intervention [37], one a text messaging program [38••], one a telephone-based motivational interviewing and coaching program [39], and the fourth a transtelephonic monitoring program [40]. Four themes were identified from the synthesis of the four articles: (1) participants reported positive usability and acceptability of the technological intervention, (2) participants desired more instruction and training in using the technology, (3) participants viewed technology as a means of providing support, (4) technologically based interventions largely improved outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, the literature related specifically to technology use for self-management in Blacks with heart failure is limited to four studies: one that investigates the use of an e-Health intervention [37], one a text messaging program [38••], one a telephone-based motivational interviewing and coaching program [39], and the fourth a transtelephonic monitoring program [40]. Four themes were identified from the synthesis of the four articles: (1) participants reported positive usability and acceptability of the technological intervention, (2) participants desired more instruction and training in using the technology, (3) participants viewed technology as a means of providing support, (4) technologically based interventions largely improved outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Heart failure patients were largely satisfied with and responded positively to the technologically based intervention [37, 38••, 39]. In the text messaging intervention, participants (n = 6) reported 100 % satisfaction with the mobile-based heart failure self-management program and said that they would recommend the program to a friend or family member [38••]; participants (n = 44) in the e-Health online management program reported high confidence with using telemonitoring devices (mean = 27.1, SD 18.9, range = 3-30) and with using web-based learning modules (mean = 7.6, SD = 3.2, range = 1-10), and stated that the program was easy to use [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] These studies showed use of SMS interventions overcame external barriers such as time and distance, but faced challenges with response rate as well as technical difficulties. 8 One study found that an SMS educational intervention had a significantly better effect on breast cancer knowledge in obstetrics-gynecology residents compared with traditional paper-based teaching.…”
Section: Current Use Of Smartphone Technology In Gmementioning
confidence: 99%
“…[21] In addition, African Americans are the largest consumers of text messaging. [22] This realization has led to the development of mHealth pilot and feasibility studies targeting heart disease management, [23] diabetes, [24] physical activity, [25,26] and weight loss maintenance. [27] Although these studies demonstrate the acceptability, feasibility, and potential effectiveness of mHealth interventions designed for African American adults, few have utilized randomized controlled designs and few were specifically designed to promote weight loss.…”
Section: Introductionmentioning
confidence: 99%